2003
DOI: 10.2337/diabetes.52.3.891
|View full text |Cite
|
Sign up to set email alerts
|

The Functional −374 T/A RAGE Gene Polymorphism Is Associated With Proteinuria and Cardiovascular Disease in Type 1 Diabetic Patients

Abstract: The hyperglycemic milieu in diabetes results in the formation of advanced glycation end products (AGEs) that predominantly act through specific receptors, particularly the receptor for AGEs (RAGE). Two functional polymorphisms in the promoter of the RAGE gene (؊429 T/C and ؊374 T/A) and one in the AGE binding domain in exon 3 (G82S) were studied in 996 Finnish type 1 diabetic patients. In patients with poor metabolic control (HbA 1c >9.5%), the AA genotype of the ؊374 T/A polymorphism was more common in those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
2
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 19 publications
4
82
2
1
Order By: Relevance
“…First, the AGER gene encoding RAGE has been associated with cardiovascular disease [2], proteinuria [2][3][4] and retinopathy [4] in patients with type 1 diabetes. Second, AGE-R1, which is encoded by DDOST, enhances the clearance of AGEs from the circulation [8], while diabetic nephropathy in patients with type 1 diabetes has been associated with low levels of AGE-R1 in circulating mononuclear cells and with elevated levels of serum AGEs [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the AGER gene encoding RAGE has been associated with cardiovascular disease [2], proteinuria [2][3][4] and retinopathy [4] in patients with type 1 diabetes. Second, AGE-R1, which is encoded by DDOST, enhances the clearance of AGEs from the circulation [8], while diabetic nephropathy in patients with type 1 diabetes has been associated with low levels of AGE-R1 in circulating mononuclear cells and with elevated levels of serum AGEs [9].…”
Section: Discussionmentioning
confidence: 99%
“…The AGER gene on chromosome 6p21 encodes the receptor for AGEs (RAGE). We have previously shown that the functional single nucleotide polymorphism (SNP) −374T/A (rs1800624) in the promoter region of AGER is associated with cardiovascular disease in Finnish patients with type 1 diabetes and with proteinuria in patients with poor glycaemic control [2]. Subsequent studies have shown that AGER is associated with diabetic nephropathy in white patients with type 1 diabetes [3,4] and with sight-threatening diabetic retinopathy in type 1 diabetes patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…The association of these promoter polymorphisms has been studied in various populations with respect to DR and other diseases, but the results are conflicting. [19][20][21] Although Indians have the largest number of diabetic patients in the world, 22,23 there is a paucity of literature on the genetic factors contributing to DR in Indians. In this study, we have examined À429 TC and À374 TA promoter polymorphisms in relation to DR in South Indian Type 2 diabetic subjects.…”
Section: Introductionmentioning
confidence: 99%
“…haplotype analysis and multi-locus association studies) it has been shown that risk variants in the RAGE gene increase the susceptibility to diabetic nephropathy and accelerate its onset (155,159) . Other studies have also identified RAGE variants as risk factors for diabetic nephropathy (160,161) .…”
Section: Advanced Glycation End Products V (Nutri)genomics and (Nutrmentioning
confidence: 98%